SCIENCE DIPLOMACY IN THE CONTEXT OF SOCIO-CULTURAL DEVELOPMENT OF EDUCATION - Perminova, Liudmila (Three seas economic journal, 2022)
The article is devoted to the problem of development of scientific diplomacy of educational institutions by means of creative cooperation. The main task of scientific diplomacy to form the image of the educational institution and interpersonal relations of all participants in the educational process is substantiated. Attention is paid to the communicative activity as a phenomenon of scientific creativity; the theoretical content of the concepts of "diplomacy", "communicative culture", "educational diplomacy" is considered; diagnostics of the readiness of educational institutions for the development of educational and scientific diplomacy is carried out. The conducted analysis of the essence of pedagogical interaction in an educational institution allows us to conclude that the concept of "educational diplomacy" is a rather complex and multifaceted concept that is used in various spheres of human activity, covers a large number of objects and phenomena, as it is manifested in the educational process, personal interaction, technological processes, communications, etc. The article also pays attention to the development of science diplomacy, peculiarities of its implementation and influence on the generation of international initiatives in the globalized world. Using a comparative methodology, the approaches to understanding science diplomacy in domestic and foreign discourse are analyzed, taking into account the existing practice of its application. It is established that science diplomacy, as a type of public diplomacy, serves as a means of promoting and protecting the national interests of the state, and also plays a regulatory role in a complex system of international interaction. At the same time, science diplomacy can serve to solve specific foreign policy tasks of regional importance – first of all with neighboring countries in the fields of ecology, forecasting and elimination of the consequences of natural and man-made disasters, mining and rational use of marine natural resources, in the social and humanitarian sphere. The availability of permanent and sufficient funding for bilateral scientific projects on such topics, especially with neighboring countries, can actually be a manifestation of scientific diplomacy for establishing good international relations. Developing the institution of science diplomacy, it is extremely important to maintain a balance of interaction between scientific and political components, to prevent the use of political tools in the scientific sphere. It is also extremely important that scientific and diplomatic goals remain transparent to avoid manipulation of science for political purposes and to prevent politicization of science. The results of the study give grounds to assert that the development of educational diplomacy is a priority area of personal development and professional development of scientists and teachers of educational institutions, based on psychological and pedagogical theory and practice and focused on subject-subject relations in work. This direction is consistently implemented in the process of studying in the system of postgraduate pedagogical education by acquiring the necessary competencies, gradual improvement of communicative qualities and accumulation of experience in communicative interaction.